The Impact of Range and Incident Angle Variation on Surface Reflectivity and Roughness-Based TLS Point Cloud Accuracy - Bakhtyar Ahmed Mala; Dleen Muhammed Salih (Eurasian Journal of Science and Engineering)
TLS has intriguing experimental procedures to investigate how various scanned surface reflectivity and roughness affected the accuracy of the scanned TLS data at various incident angles and ranges. Thus, different materials (glass, steel, wood, Ekoplast, and the sheet target of the total station) were used. During the experiment, four distinct ranges (5 m, 20 m, 40 m, and 60 m) under the same weather conditions were employed. The selected materials were scanned at 6 incident angles from 0˚ to 75˚, rotating 15˚ per scan. This means a total of 96 scans were measured. At various scan angles and ranges, smooth surfaces have a greater effect on the quality of the scanned data than rough surfaces. The whole Total Station (TS) target reflects approximately 200mm closer to the instrument at 0˚ incident angle than the other materials at the 5m range; this difference decreases as the incident angle increases. On the other hand, this difference also decreases with increasing the range; at 0˚ and 5m range, it’s about 200mm, while for the same angle and 60m range, it's about 120mm. Furthermore, the density of the point clouds decreases with increasing range. Finally, the effect of the distance clearly appeared on the small incident angle rather than the large incident angle.